2023
DOI: 10.3831/kpi.2023.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Clinical and Preclinical Studies on the Therapeutic Potential of Black Seeds (Nigella sativa) in the Management of Polycystic Ovarian Syndrome (PCOS)

Abstract: Objectives: Polycystic ovary syndrome (PCOS) is a condition that occurs frequently among women of reproductive age and is a polygenic, multifactorial, endocrine, and metabolic disorder. PCOS is becoming more common as a result of risk factors such as current lifestyle, overnutrition, and stress. The use of traditional herbal medicine is higher among the global population. Hence, this review article focuses on the potential of Nigella sativa to manage women with PCOS. Methods: A literature search was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In clinical studies, Nigella sativa and its constituents, including TQ, have demonstrated antimicrobial, antioxidant, anti-inflammatory, anticancer and anti-diabetic properties, as well as therapeutic effects on metabolic syndrome and gastrointestinal, neural, cardiovascular, respiratory, urinary and reproductive disorders [54]. Recent clinical trial reports suggest the potential use of Nigella sativa in complementary treatment and prevention of conditions such as coronary artery disease, diabetic peripheral neuropathy, Helicobacter pylori infection and polycystic ovary syndrome [60][61][62][63]. The safety of thymoquinone-rich black cumin oil was evaluated in a phase I clinical trial and provided satisfactory results [64].…”
Section: Preclinical and Clinical Studies On Thymoquinone And Its Mai...mentioning
confidence: 99%
“…In clinical studies, Nigella sativa and its constituents, including TQ, have demonstrated antimicrobial, antioxidant, anti-inflammatory, anticancer and anti-diabetic properties, as well as therapeutic effects on metabolic syndrome and gastrointestinal, neural, cardiovascular, respiratory, urinary and reproductive disorders [54]. Recent clinical trial reports suggest the potential use of Nigella sativa in complementary treatment and prevention of conditions such as coronary artery disease, diabetic peripheral neuropathy, Helicobacter pylori infection and polycystic ovary syndrome [60][61][62][63]. The safety of thymoquinone-rich black cumin oil was evaluated in a phase I clinical trial and provided satisfactory results [64].…”
Section: Preclinical and Clinical Studies On Thymoquinone And Its Mai...mentioning
confidence: 99%
“…PCOS women with hyperandrogenism along with IR have the predilection for visceral fat hypertrophy apart from early initiation of dysfunctional glucose tolerance test exists in 30-40%, T2D in 10%, borderline or escalated lipid quantities in 70% in addition to metabolic syndrome [MetS] in 50% [64]. Thereby PCOS is intricately associated with metabolic abnormalities along with is believed to be a metabolic condition [65]. Moreover, PCOS is correlated with dysfunctional AT physiology as well as possesses greater risk of nonalcoholic fatty liver disease (NAFLD) generation [66,67].…”
Section: More Channelsmentioning
confidence: 99%